Mythology And Culture: Implication Of Female Genital Mutilation In Urhobo Land (Journal of Namibian Studies : History Politics Culture, 2023)
Female genital mutilation (FGM) has attracted international attention in recent times, and the formulation of new laws against the practice in Nigeria. While there have been little changes in the frequency of the exercise in many parts of the country there is evidence of prevalence among young people in Urhobo land in the rural areas. There has been a lower presence among daughters of educated mothers in the urban areas in Urhobo land. This challenge has necessitated the increasing research and policy changes to address these issues. Proponents of FGM in Urhobo land believe that there is a myth behind it and should therefore not be questioned nor stopped. They itemised social, psychological, and cultural benefits of which include conformity to social pressure and peers; raise a girl properly and prepare her for adulthood and deliver her from marital failures; reduces women sexual desires thereby preventing promiscuity; religious beliefs; sexual restraints; cleanliness, neatness and beautifying of females’ sexual organs. Global outcry against FGM condemn the practice believing that it has no health benefit since (i) it is violent against women as it leads to childbirth complications. (ii)death rate of babies such as neonatal death. (iii)sexual problems. (iv)outbreak of infections and could lead to Cervical cancer. The paper employed the qualitative research methodology and focus group discussion to achieve the objectives of the study.